Analysis of Wave Propagation in Detection of Aorta Dieses Using Lumps Analysis - Al-Jumaily, A. M; Al-Ammri, A. Salam (Al-Khwarizmi Engineering Journal, 2009)
In this paper a theoretical attempt is made to determine whether changes in the aorta diameter at different location along the aorta can be detected by brachial artery measurement. The aorta is divided into six main parts, each part with 4 lumps of 0.018m length. It is assumed that a desired section of the aorta has a radius change of 100,200, 500%. The results show that there is a significant change for part 2 (lumps 5-8) from the other parts. This indicates that the nearest position to the artery gives the significant change in the artery wave pressure while other parts of the aorta have a small effect.